Clinical efficacy of adjunctive methods for the non-surgical treatment of peri-implantitis: a systematic review and meta-analysis (2023)
Background: The aim of this systematic review (SR) was to evaluate the clinical efficacy of different adjunctive methods/therapies to the non-surgical treatment (NST) of peri-implantitis. Materials and methods: The protocol of the review was registered in PROSPERO database (CRD42022339709) and was designed according to PRISMA statement. Electronic and hand searches were performed to identify randomized clinical trials (RCTs) comparing non-surgical treatment of peri-implantitis alone versus NST plus any adjunctive method/treatment. The primary outcome was probing pocket depth (PPD) reduction. Results: Sixteen RCTs were included. Only 2 out of 1189 implants were lost and follow-up ranged from 3 to 12 months. PPD reduction across the studies varied from 0.17 to 3.1 mm, while defect resolution from 5.3% to 57.1%. Systemic antimicrobials were associated to higher PPD reduction (1.56 mm; [95% CI 0.24 to 2.89]; p = 0.02) with high heterogeneity, and treatment success (OR = 3.23; [95% CI 1.17 to 8.94]; p = 0.02), compared to NST alone. No differences were found with adjunctive local antimicrobials and lasers for PPD and bleeding on probing (BoP) reduction. Conclusions: Non-surgical treatment with or without adjunctive methods may reduce PPD and BoP even if complete resolution of the pocket is unpredictable. Among possible adjunctive methods, only systemic antibiotics seems to provide further benefits, but their usage should be considered with caution.